Shielded hydrogen plasma: a new hydrogenation method for silicon solar cells - Bourret-Sicotte, GA (2019)
Improving the efficiency of solar cells will play a key role in ensuring that solar generated power reaches grid-parity across the globe. One of the main challenges in achieving high-efficiency silicon cells is the recombination of minority carriers at defects, both at the silicon surface and throughout the bulk. Introducing hydrogen into silicon is a well-recognised method to achieve excellent chemical passivation of surface and bulk defects.